Potential of Herbal Tea Based On Soursop (Annona Muricata L.) Leaf Extract in Reducing Psychological Stress Through the Activity of Flavonoid Compounds on Neurotransmitter Regulation and Cellular Oxidation - Carissa Almaira Ramadhani; Putri Atsiil Zailianti; Rella Insani Fitri (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
This study aims to determine the effect of soursop leaf herbal tea consumption on reducing stress levels among new students at MAN Insan Pakar OKI. The research employed a laboratory and field experimental method using a One-Group Pre-Test-Post-Test Design. The stages included the preparation of soursop leaf tea, phytochemical tests (Benedict, FeCl₃, and saponin), microbiological tests (TPC, Salmonella sp., and E. coli), and psychological assessment using the DASS-42 questionnaire. A total of 90 respondents consumed one cup of soursop leaf tea daily for seven days, with stress levels measured before and after the intervention. The results indicated a significant decrease in DASS-42 scores (t = 9.12; p < 0.001) with a large effect size (Cohen's d = 1.15). These findings suggest that soursop leaf tea has the potential to serve as a functional herbal beverage that is safe for consumption and supports students' psychological well-being in adapting to a boarding school environment.